The Effects of Implementing Clinical Supervision Model on Supervisors’ Teaching Perspectives and Qualifications: A Case Study in an EFL Context - Ehsan Khaef (Hindawi Limited, 2021)
This study set out to determine the possible impacts of implementing the Clinical Supervision Model (CSM) on supervisors’ philosophy of teaching, in both theory and practice. In order to gather the required data, two highly experienced supervisors were recruited according to the degree of homogeneity of the educational context in which they were working. By applying qualitative case study design, the required data were collected by conducting two distinct phases of classroom observations, accompanied by semistructured interviews. Considering the nature of the investigation, it was decided to employ the Transcendental Phenomenology (TPh) approach to analyze the data in order to determine the supervisors’ accurate perceptions and lived experiences regarding the nature of taking on a supervisory role and the effects of implementing CSM on their teaching career. The empirical findings in this investigation provided a new understanding of the probable effects of implementing CSM on supervisors’ general attitudes towards both teaching and supervisory careers. The results of the study indicated that CSM can be potentially effective in encouraging critical thinking, providing more constructive feedback in postobservation meetings, and improving the teaching quality of both teachers and supervisors.